Preparation of Silver Nanoball@GNSs Lubricant and its Antifriction under Current Carrying - Liu, Chunying; Yang, Duo (International Journal of Mechanical and Electrical Engineering, 2025)
In this experiment, silver nanoball@ graphene nanosheets (SG) composite additive using under a current-carrying was prepared via in-situ reduction method, which has both good electrical conductivity and tribological properties. The conductivity test results showed a 12-fold increase in the conductivity of the novel composite compared to the pure ionic liquid LP108. Without the current carrying, the values of COF were decreased to 0.070 and the wear volume of the disk was reduced by 88.4% at an additive concentration of 0.10 wt%. when a 1A current was applied to both ends of the friction pair,the average COF of the lubricant material was as low as 0.06892 with a 78.6% reduction in wear. This is because the movement of anions and cations in the ionic liquid can be accelerated by the electric current, and Ag and C elements in the additive can be adsorbed on the surface of the friction pair to form a protective film. This research result opens up a new way to improve the tribological properties of sliding electrical contacts from micro and nano scale technology and to develop a new generation of highly conductive lubricant materials.